Clinical and pathological features of bronchiolitis obliterans requiring lung transplantation in paraneoplastic pemphigus associated with Castleman disease. (21st January 2022) - Chen, Wenhui; Zhao, Ling; Guo, Lijuan; Zhao, Li; Niu, Hongtao; Lian, Huifang; Dai, Huaping; Chen, Jingyu; Wang, Chen
Abstract: Summary at a glance: Bronchiolitis obliterans in paraneoplastic pemphigus associated with Castleman disease possesses the progressive nature even when it is treated with intensive medical therapy. Antibodies were at least in low titers before the Lung transplant and remain negative after the procedure. Explanted lungs showed coexistence of cellular destructive bronchiolitis and constrictive bronchiolitis. Background: Bronchiolitis obliterans (BO) in paraneoplastic pemphigus (PNP) associated with Castleman disease (CD) possesses the progressive nature of pulmonary disease even when it is treated with intensive medical therapy. Lung transplantation (LT) offers an acceptable form of treatment. Methods: We conducted a retrospective study of two cases of BO in PNP associated with CD who underwent LT between March 2017 and March 2020 at the China‐Japan Friendship Hospital. We also included one case from the literature. Results: In this patient series, PNP was the primary clinical presentation in all patients, and it was accompanied by respiratory symptoms before/after CD excision. In spite of being treated with various combinations of immunosuppressive and anti‐inflammatory agents, the patients had great or total improvement in mucosal erosions, whereas their pulmonary function test (PFT) deteriorated gradually or sharply. The duration times from disease onset to timing of LT were 1, 2 and 5 years. All antibodies were negative or were present at low titers before the LT procedure and remain negative after the procedure. The histopathological features of explanted lungs showed cellular and coexistent destructive bronchiolitis and constrictive bronchiolitis in two cases. Granulation with numerous foamy macrophages, scattered giant cells and cholesterol clefts were especially prominent in case one. Conclusion: BO in PNP associated with CD had poor clinical outcomes. LT was preferable choice in end‐stage BO when PNP and CD were controlled.